Green writing: the influence of natural spaces on primary students’ poetic writing in the UK and Australia - Gardner, P.; Kuzich, Sonja (Routledge, 2017)
© 2017 University of Cambridge, Faculty of Education This paper draws on findings of comparative international research on students’ poetic writing about the natural environment in the context of the classroom and a naturalistic setting. The study involved 97, nine- to 10-year-olds in four classes: two classes were in an English primary school with their counterparts in a Western Australian primary school. One class in each school had vicarious contact with nature as a stimulus for writing, using a previously taught technique for writing poetry; the other class in each school used the same technique but had direct contact with nature. The study has implications for students’ literacy development, creativity and agency and suggests that students’ poetic writing is enhanced through direct contact with nature. Teachers in both England and Australia, countries where ‘high stakes’ testing dominates the literacy curriculum, may find that standards of writing improve when students are given direct contact with natural spaces and are scaffolded to elicit their poetic voice.